Aortocaval fistula and celiac artery transection after gunshot wound. Issue 5 (November 2016) - Yon, James R.; Fredericks, Charles; Starr, Frederic; Bokhari, Faran; Moore, Laura J.
Abstract : Supplemental digital content is available in the text.